2018
DOI: 10.1038/s41598-018-34185-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced excitonic emission efficiency in porous GaN

Abstract: We investigate the optical properties of porous GaN films of different porosities, focusing on the behaviors of the excitonic features in time-integrated and time-resolved photoluminescence. A substantial enhancement of both excitonic emission intensity and recombination rate, along with insignificant intensity weakening under temperature rise, is observed in the porous GaN films. These observations are in line with (i) the local concentration of electric field at GaN nanoparticles and pores due to the depolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…This emission is three times higher than undoped MAPbI 3 thin film. The results could be attributed to reducing trap density states with decreased charge recombination, which improved the thin film's optoelectronic properties (Brennan et al, 2017;Ngo et al, 2018).…”
Section: Optical and Photoluminescence Studymentioning
confidence: 99%
“…This emission is three times higher than undoped MAPbI 3 thin film. The results could be attributed to reducing trap density states with decreased charge recombination, which improved the thin film's optoelectronic properties (Brennan et al, 2017;Ngo et al, 2018).…”
Section: Optical and Photoluminescence Studymentioning
confidence: 99%
“…The quality and the existence of defects in materials can be detected clearly by PL spectroscopy. 22,[23][24] It is a good scientific tool to assess the quality of materials, also many parameters can be calculated from PL spectra.…”
Section: Introductionmentioning
confidence: 99%
“…28 Similarly, a high temperature thermal treatment of GaN layers can be applied to induce the porosification of the layers under a H2 atmosphere in a hydride vapor phase epitaxy reactor or a metal-organic vapor-phase epitaxy reactor, 29,30 or alternatively under a N2 atmosphere in a resistance furnace 31 or eventually under vacuum in a molecular beam epitaxy reactor after the deposition of a SixNy nanomask. 32,33,34 Through this last approach, we showed that the photoluminescence efficiency at room temperature of highly dislocated GaN layers was strongly increased when they were porosified. We previously attributed this improvement to the preferential sublimation of GaN around dislocations but with only indirect elements supporting this hypothesis.…”
Section: Introductionmentioning
confidence: 99%